2014
DOI: 10.1007/s10646-014-1281-z
|View full text |Cite
|
Sign up to set email alerts
|

Responses of sympatric Karenia brevis, Prorocentrum minimum, and Heterosigma akashiwo to the exposure of crude oil

Abstract: Impacts of the Deepwater Horizon oil spill on phytoplankton, particularly, the tolerability and changes to the toxin profiles of harmful toxic algal species remain unknown. The degree to which oil-affected sympatric Karenia brevis, Prorocentrum minimum, and Heterosigma akashiwo, all of which are ecologically important species in the Gulf of Mexico, was investigated. Comparison of their tolerability to that of non-toxic species showed that the toxin-production potential of harmful species does not provide a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…However, the extent to which phytoplankton are impacted by crude oil can largely depend on the toxicological potency and concentration of the oil (Dunstan et al ., ; Vargo et al ., ; Bate and Crafford, ; Huang et al ., ). Different phytoplankton species can have varying tolerances to oil (Ozhan and Bargu, ), and some may even be stimulated by it (Prouse et al ., ; Jung et al ., ; Parsons et al ., ). The most toxigenic hydrocarbons in crude oils are those comprising the aromatic fraction – i.e., mono‐aromatics and PAHs – which are recognized as high‐priority pollutants to the environment (Agency for Toxic Substances and Disease Registry, ; Boehm and Page, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the extent to which phytoplankton are impacted by crude oil can largely depend on the toxicological potency and concentration of the oil (Dunstan et al ., ; Vargo et al ., ; Bate and Crafford, ; Huang et al ., ). Different phytoplankton species can have varying tolerances to oil (Ozhan and Bargu, ), and some may even be stimulated by it (Prouse et al ., ; Jung et al ., ; Parsons et al ., ). The most toxigenic hydrocarbons in crude oils are those comprising the aromatic fraction – i.e., mono‐aromatics and PAHs – which are recognized as high‐priority pollutants to the environment (Agency for Toxic Substances and Disease Registry, ; Boehm and Page, ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, field and laboratory studies have shown that crude oil concentrations up to 1.0 mg/l can stimulate phytoplankton growth – a phenomenon that may have an origin in ocean systems distinguished by the occurrence of natural hydrocarbon seeps on the sea floor where elevated surface chlorophyll concentrations have been reported (D'souza et al ., ). Higher crude oil concentrations, however, can cause anywhere from slight, severe to complete growth inhibition of phytoplankton (Nomura et al ., ; Adekunle et al ., ; Gilde and Pinckney, ; González et al ., ; Paul et al ., ; Ozhan and Bargu, ; Ozhan et al ., ). The consequences of crude oil pollution at sea to phytoplankton must also take into account the associated bacterial community.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Observational studies also suggest that levels of potentially harmful algae can increase from oil spills, as reported with reference to the presence of Itxoc I in the Gulf of Mexico in 1979 [56], the Deepwater Horizon oil spill in Offshore Florida, Gulf of Mexico in 2010 [57] and by the Bohai Sea spill in China in 2011) [58]. The effects vary based on oil concentrations [59,60], use of dispersants [61], nutrientlimited circumstances [62], and types of oil [63,64]. Ozhan and Bargu [59] showed increased levels of okadaic acid with increased levels of crude oil, which can further contaminate shellfish and threaten the health of shellfish consumers.…”
Section: Food Sovereignty For the Tsleil-waututh Nation (Twn): Chemicmentioning
confidence: 95%
“…Several previous studies have examined the effects on individual phytoplankton species of crude oil [11][12][13][14][15][16][17], various components of crude oil [18][19][20][21][22][23], and refined oil products [23][24][25][26][27]. The general implication of these studies has been that low concentrations of crude oil or components thereof stimulate photosynthesis by some species [13,19,23] but have no positive effect on other species.…”
Section: Introductionmentioning
confidence: 99%